2018
DOI: 10.1109/tit.2018.2791994
|View full text |Cite
|
Sign up to set email alerts
|

The Capacity of Private Information Retrieval From Coded Databases

Abstract: We consider the problem of private information retrieval (PIR) over a distributed storage system. The storage system consists of N non-colluding databases, each storing a coded version of M messages. In the PIR problem, the user wishes to retrieve one of the available messages without revealing the message identity to any individual database. We derive the information-theoretic capacity of this problem, which is defined as the maximum number of bits of the desired message that can be privately retrieved per on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
411
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 351 publications
(416 citation statements)
references
References 19 publications
4
411
0
1
Order By: Relevance
“…From [5], we know that the capacity of MDS-PIR with (K, N, K c ) = (2, 4, 3) is 4/7. Therefore, the upper bound follows.…”
Section: Disjoint Colluding Sets Of T Servers Eachmentioning
confidence: 99%
See 1 more Smart Citation
“…From [5], we know that the capacity of MDS-PIR with (K, N, K c ) = (2, 4, 3) is 4/7. Therefore, the upper bound follows.…”
Section: Disjoint Colluding Sets Of T Servers Eachmentioning
confidence: 99%
“…The capacity achieving scheme of Banawan and Ulukus [5] improved upon a scheme proposed earlier by Tajeddine and Rouayheb in [7]. Tajeddine and Rouayheb also proposed an achievable scheme for MDS-TPIR for the T = 2 setting.…”
Section: Introductionmentioning
confidence: 98%
“…denotes the set of all possible queries made by the user. Although this seems to be intuitively true, a proof of this property is still required and can be found in [13].…”
Section: A General Conversementioning
confidence: 99%
“…In [16], it is shown that the MDS-PIR capacity [13] can be achieved using Protocol 1 for a special class of [n, k] codes. In particular, to achieve the MDS-PIR capacity using Protocol 1, the [n, k] storage code should possess a specific underlying structure as given by the following theorem.…”
Section: Mds-pir Capacity-achieving Codesmentioning
confidence: 99%
“…In a system consisting of n replicated servers, the user sends homomorphically encrypted queries 32,43 to the n servers to retrieve data blocks from the servers that collectively make up the result. In a system consisting of n replicated servers, the user sends homomorphically encrypted queries 32,43 to the n servers to retrieve data blocks from the servers that collectively make up the result.…”
Section: Shortcomings Of Searchable Encryption Systemsmentioning
confidence: 99%